Enhancing Smart City Services with AI: A Field Experiment in the Context of Industry 5.0 - Natalia Taskaeva; Kumar Joshi Sanjeev; Dixit Saurav; Kanakadurga Bella H.; Chandra Jena Prakash; Vyas Anjali (BIO Web of Conferences, 2024)
The practical effects of incorporating artificial intelligence (AI) into Industry 5.0 smart city services are made evident by this empirical research. The use of AI-powered smart traffic management yields a noteworthy 32.94% rise in traffic volume, signifying a noteworthy progression towards improved urban mobility. AI waste management optimization results in a 5.71% increase in collection efficiency, highlighting the importance of operational effectiveness and resource conservation. The control of energy use shows an 8.57% decrease, confirming AI's importance in sustainable energy practices. AI-enhanced public safety offers dependable event prediction, indicating safer cityscapes. These results highlight AI's revolutionary potential and establish smart cities as safe, secure, and sustainable urban environments.